Riesgos ergonómicos y trastornos musculoesqueléticos en cirujanos. - Yopla-Sevilla, A.M (2024)
Ergonomic risks in surgery can have a significant impact on the musculoskeletal health of surgeons, increasing the prevalence of musculoskeletal disorders (MSDs) and affecting their ability to work effectively and safely. This is compounded by the introduction of technologies such as video-assisted surgery and robotics, which although offer advantages in precision, can increase fatigue and muscle stress. Additionally, different surgical specialties face unique challenges, such as prolonged postures and delicate movements in neurosurgery, and manipulation of heavy instruments in orthopedic surgery. It is essential to increase ergonomic awareness among surgeons and provide specific training during their training, as well as improve the ergonomic design of operating rooms and select ergonomic surgical equipment. Continued research and intervention evaluation are critical to developing effective TME prevention strategies in surgeons.